Enhancing feasibility when measuring teachers' motivation: A brief scale for teachers' achievement goal orientations. (July 2019) - Janke, Stefan; Bardach, Lisa; Oczlon, Sophie; Lüftenegger, Marko
Abstract: We developed a brief questionnaire for teachers' achievement goal orientations that allows for an accurate assessment, while also being feasible for complex research designs. In a first online study with 502 German teachers, we investigated the scale's factorial structure, its measurement invariance over different career stages and its construct validity. In a second study with 650 Austrian teachers, we tested its concurrent validity for teachers' self-efficacy, attitudes toward vocational help-seeking and achievement emotions. The results of both studies show that this short scale is characterized by high reliability, validity and feasibility for a wide array of studies on teachers' motivation. Highlights: We developed a short scale to measure teachers' achievement goal orientations. The scale is reliable and measurement invariant over career stages (study 1). We found a meaningful pattern of convergent and discriminant validity (study 1). The scale is also characterized by strong predictive validity (study 2). In sum, it allows for high measurement accuracy and feasibility for field research.